Discrete probability model-based method for recognition of multicomponent combustible gas explosion hazard sources - Ye Wenhua; Feng Yang; Chen Yangming (High Temperature Materials and Processes, 2022)
Aiming at the problems of poor sensitivity and low accuracy of traditional combustible gas explosion hazard identification methods, the discrete probability model was introduced to design a multicomponent combustible gas explosion hazard identification method. Fem3 model is selected to analyze the diffusion mode of multicomponent combustible gas, and the calculation formula of diffusion velocity is obtained. The explosion limit of multicomponent combustible gas was observed by means of test, and the upper limit of explosion concentration of multicomponent combustible gas was obtained. According to the characteristics of explosion, a multicomponent combustible gas explosion hazard identification device is designed. The discrete probability model is used to identify the explosion hazard of multicomponent combustible gas. Experimental results show that the proposed method greatly improves the recognition sensitivity and accuracy, which fully shows that the proposed method has a better detection effect.